2010
DOI: 10.1111/j.1600-0609.2010.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Cladribine combined with rituximab (R-2-CdA) therapy is an effective salvage therapy in relapsed or refractory indolent B-cell non-Hodgkin lymphoma

Abstract: Although cladribine has been reported to be an active purine analog against indolent B-cell non-Hodgkin lymphoma (B-NHL), there are few reports of combination use of cladribine and rituximab. This multicenter phase II study evaluated the efficacy and toxicity of cladribine with rituximab (R-2-CdA) therapy in relapsed or refractory indolent B-NHL. Twenty patients with the median age of 58.5 yrs (range, 42-72) were enrolled and received R-2-CdA therapy from April 2005 to July 2007. The median number of prior reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[1416] Intravenous cladribine produces response rates of 30–45%, also increased when combined with rituximab. [1719] While the majority of chemotherapy agents employed for relapsed/refractory NHL are administered intravenously, patients may prefer oral agents provided they offer similar therapeutic efficacy. [20] An oral formulation of fludarabine was reported to show an overall response rate of 65% in a phase 2 trial in relapsed indolent B-cell NHL, though 70% of patients experienced grade 3 or 4 neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…[1416] Intravenous cladribine produces response rates of 30–45%, also increased when combined with rituximab. [1719] While the majority of chemotherapy agents employed for relapsed/refractory NHL are administered intravenously, patients may prefer oral agents provided they offer similar therapeutic efficacy. [20] An oral formulation of fludarabine was reported to show an overall response rate of 65% in a phase 2 trial in relapsed indolent B-cell NHL, though 70% of patients experienced grade 3 or 4 neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Hirokazu et al reported high efficacy of R-2-CdA therapy as a salvage approach relapsed or refractory indolent B-NHL, with a ORR of 90% and CR of 70%. However, the 20-patient cohort in this study was mainly comprised by patients with follicular lymphoma, and only consisted 2 with MALT lymphoma (25). In a retrospective study involving 89 patients with marginal zone lymphoma, the use of R-2-CdA therapy resulted in an ORR of 89.3%, with 53.6% CR and 60 months of median of TTP, and a trend of early relapse in patients who did not receive rituximab was reported (44).…”
Section: Discussionmentioning
confidence: 94%
“…Monotherapy of cladribine is now considered the standard first-line treatment for hairy cell lymphoma (37,38). In addition, cladribine had shown satisfying effects in other indolent type of B-cell neoplasms, including marginal zone lymphoma, both as a single agent and in combination with other agents (22,24,25,34). Prolonged efficacy and longterm safety had been reported for cladribine in several publications (23,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one patient, however, 2-CdA was delivered subcutaneously due to lack of venous access. In another patient, 2-CdA was delivered daily over 5 days as iv infusion over 2 hours according to Nagai et al [ 25 ]. Toxicity was graded according to the US National Cancer Institute using the Common Terminology Criteria for Adverse Events (CTCAE) version 4.03.…”
Section: Methodsmentioning
confidence: 99%